Break‐even analysis for the storage of PV in power distribution grids. (7th October 2013) - Nykamp, Stefan; Bakker, Vincent; Molderink, Albert; Hurink, Johann L.; Smit, Gerard J.M.
SUMMARY The integration of renewable energy systems poses major challenges on distribution grid operators. Because of the strong growth rates of the installation of photovoltaic (PV) and wind generators, huge needs for reinforcements in grids are expected. Next to conventional reinforcements (with additional and/or bigger dimensioned cables and transformers) also the introduction of decentralized storage systems seems to be promising. In this paper, an economical approach is presented enabling the calculation of break‐even points for storage systems as a substitute to conventional grid reinforcements. The dynamic profitability calculation considers main influencing cost drivers for both alternatives, including operational and capital expenditures. Furthermore, the calculation of benefits of decentralized storage systems for upstream grid levels is also integrated. To enable these calculations, a storage model is derived oriented on battery characteristics to determine main requirements of a storage system to be able to integrate renewable energy systems. These elaborations are reflected on a real‐world distribution grid faced with reinforcement needs due to the integration of PV. For this, measured data for the PV generator are integrated as well. The analysis reveal break‐even points for the storage asset ranging between 100 and 500 € per kWh of installed capacity, depending on the lifetime of the storage asset and the costs for the substitute. Furthermore, main influencing parameters are evaluated using a sensitivity analysis. It is shown that the profitability can be increased significantly if not all peaks of PV generation need to be stored. Furthermore, the analysis of the operation for 1 year indicates that a combined operation of the storage asset (not only oriented on grid objectives such as peak shaving, but considering also the objectives of further stakeholders such as energy traders) seems to be reasonable for increasing the profitability and incentivizing a larger market penetration of storage assets. Copyright © 2013 John Wiley & Sons, Ltd.